The effect of a period of water shortage on the growth and yield of cassava - Connor, D. (International Center for Tropical Agriculture, 1980)
Drought stress was imposed on 2 cassava cv. (M Col 22 and M Mex 59) at Santander de Quilichao (Colombia), by withholding rainfall from field plots (plastic covers were placed over the soil surface) for 10 wk, commencing when crops were 12 wk old. The plants were then allowed to recuperate until the expt was terminated at 10 mo. Harvests were taken at intervals through the growth cycle and were supplemented with measurements of fine root distribution, leaf production and senescence, soil and plant water status, and stomatal response. As a result of the stress, the late-developing cv. M Mex 59 actually improved its yield at 10 mo over the controls. An explanation for the behavior of both cv. is sought in the relative effects of water shortage on DM production and allocation, canopy dynamics and internal plant water relations. (AS)